Investigation of sestrin-2 levels and thiol-disulfide homeostasis in polyp tissue of patients with nasal polyps - Zainab KH Abdulrahman ABDULRAHMAN; Hasan Inco; Kenan Ercan; Ismail Aytac; Seyithan Taysi (Scientific Reports)
Abstract Nasal polyposis (NP), a chronic inflammatory disease of the upper respiratory tract, has a poorly understood pathophysiology and no etiological factors explaining its pathogenesis, but inflammation remains an important factor. Sestrins (SESNS), which are conserved antioxidant proteins that accumulate in cells in response to various stresses, regulate the regulatory roles of SESN2 in the immune system and inflammatory responses. In the current study, we aimed to investigate the sestrin-2 pathway, oxidative stress and thiol-disulfide homeostasis in NP tissue of patients. The study included a total of 90 participants with the age 12–65 years. The patient group consisted of 45 patients diagnosed with NP and free from chronic disease. The control group comprised 45 patients who underwent nose surgery for anatomical pathology other than NP. The levels of native thiol, total thiol, disulfide, disulfide/native thiol and disulfide/total thiol were found to be significantly higher in the patient group, while native thiol/total thiol levels were lower when compared to the control group. Besides, the levels of total oxidant status (TOS) and oxidative stress index (OSI) were significantly higher while total antioxidant status (TAS) levels were significantly lower compared to the control group. Also, extracellular signal-regulated kinase 1/2 (ERK1/2) levels were found to be higher and SESN2 lower than those in control group. The findings show that decreased SESN2, TAS levels and increased ERK1/2, TOS and OSI levels and impaired thiol-disulfide homeostasis in polyp tissues of patients with NP cause oxidative stress.